Improving the Methodology of Teaching the Laws of Thermodynamics in Secondary Schools - Razaqov Jasur Xolmirzoyevich; Ochildiyeva Hilola Toshtemir kizi (Zien Journals, 2022)
This article describes the combination of knowledge, skills and abilities acquired by students in the physical essence of the first law of thermodynamics based on modern educational technologies.
Keywords: thermodynamics; amount of heat; internal energy